Spatial and temporal variation of Antarctic microbial interactions: a study around the west Antarctic Peninsula - Swan L. S. Sow; Willem H. van de Poll; Rachel Eveleth; Jeremy J. Rich; Hugh W. Ducklow; Patrick D. Rozema; Catherine M. Luria; Henk Bolhuis; Michael P. Meredith; Linda A. Amaral-Zettler; Julia C. Engelmann (Environmental Microbiome)
Abstract Background The west Antarctic Peninsula (WAP) is a region of rapid environmental changes, with regional differences in climate warming along the north–south axis of the peninsula. Along the WAP, Palmer corresponds to a warmer region with lesser sea ice extent in the north compared to Rothera ~ 400 km to the south. Comprehensive and comparative, year-round assessments of the WAP microbial community dynamics in coastal surface waters at these two locations are imperative to understand the effects of regional climate warming variations on microbial community dynamics, but this is still lacking. Results We report on the seasonal diversity, taxonomic overview, as well as predicted inter-and intra-domain causal effects (interactions) of the bacterial and microbial eukaryotic communities close to the Palmer station and at the Rothera time-series site between July 2013 and April 2014. Our 16S- and 18S-rRNA gene amplicon sequencing data showed that across all seasons, both bacteria and microbial eukaryotic communities were considerably different between the two sites which could be attributed to seawater temperature, and sea ice coverage in combination with sea ice type differences. Overall, in terms of biotic drivers, causal-effect modelling suggests that bacteria were stronger drivers of ecosystem dynamics at Palmer, while microbial eukaryotes played a stronger role at Rothera. The parasitic taxa Syndiniales persevered at both sites across the seasons, with Palmer and Rothera harbouring different key groups. Up to 62.3% of the negative causal effects were driven by Syndiniales at Rothera compared to only 13.5% at Palmer, suggesting that parasitism drives community dynamics at Rothera more strongly than at Palmer. Conversely, SAR11 Clade II, which was less abundant but persistent year-round at both sites, was the dominant driver at Palmer, evidenced by many (28.2% and 37.4% of positive and negative effects respectively) strong causal effects. Article note: Kindly check first page article notes are correct. Conclusions Our research has shed light on the dynamics of microbial community composition and correlative interactions at two sampling locations that represent different climate regimes along the WAP.